2018
DOI: 10.1111/epi.14530
|View full text |Cite
|
Sign up to set email alerts
|

Return of individual results in epilepsy genomic research: A view from the field

Abstract: Genomic findings are emerging rapidly in 2 large, closely related epilepsy research consortia: the Epilepsy Phenome/Genome Project and Epi4K. Disclosure of individual results to participants in genomic research is increasingly viewed as an ethical obligation, but strategies for return of results were not included in the design of these consortia, raising complexities in establishing criteria for which results to offer, determining participant preferences, managing the large number of sites involved, and coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Currently, most research ethics committees (RECs) institutions require researchers to engage the communities before commencing and upon completion of studies [ 23 , 28 , 54 58 ]. Due to the variability of research results and the lack of reference information, participants should be allowed to choose which results to receive during the consenting process [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most research ethics committees (RECs) institutions require researchers to engage the communities before commencing and upon completion of studies [ 23 , 28 , 54 58 ]. Due to the variability of research results and the lack of reference information, participants should be allowed to choose which results to receive during the consenting process [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics are presented for survey responses, stratified by sociodemographic and clinical covariates: sex, age, study site, cohort (enriched or standard), self-reported race (white, black, Asian, or other) and ethnicity (Hispanic or non-Hispanic), income, and education level. For the three main outcomes, multivariable logistic regression models adjusted for these a priori selected sociodemographic and clinical covariates, based on the researcher's knowledge and prior literature, are presented as odds ratios with 95% confidence intervals [7][8][9][10][11][12][13][14][15]. All quantitative analyses were conducted on Python (v2.7.1); a nominal p-value (i.e., unadjusted for multiple comparisons) of <0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, calls for a more participant-centric research approach have included support for the belief that participants have a right to their health data and that investigators have an obligation to return research results to participants [7][8][9][10]. Prior work on returning single data types, such as imaging and genetic data, has shown promising but mixed results, with the opportunity to create value intermixed with cautionary notes of potential harms [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Discovery of a molecular genetic cause for a type of epilepsy, and determination of the molecular genetic cause of an individual's epilepsy, has been heralded as the end of the diagnostic odyssey. 32 It is also the start of another, different, set of journeys and questions, which are likely to be complex, and for most of which we have not yet scoped out the landscape and may not yet have the tools to navigate 33,34 : in this context, the GLUT1 deficiency syndrome, for which ketogenic dietary treatments are often considered precision medicine, has been thoughtfully reconsidered. 35 In our current paradigm, the necessary first step after gene discovery is to secure functional evidence that the putatively pathogenic variants identified in the gene have a consequence.…”
Section: S97mentioning
confidence: 99%